Effect of added dietary threonine on growth performance, health, immunity and gastrointestinal function of weaning pigs with differing genetic susceptibility to Escherichia coli infection and challenged with E. coli K88ac. Issue 3 (26th June 2014) - Trevisi, P.; Corrent, E.; Mazzoni, M.; Messori, S.; Priori, D.; Gherpelli, Y.; Simongiovanni, A.; Bosi, P.
Summary: Threonine (Thr) is important for mucin and immunoglobulin production. We studied the effect of added dietary Thr on growth performance, health, immunity and gastrointestinal function of weaning pigs with differing genetic susceptibility to E. coli K88ac (ETEC) infection and challenged with ETEC. Forty‐eight 24‐day‐old weaned pigs were divided into two groups by their ETEC susceptibility using mucin 4 (MUC4) gene as a marker (2 MUC4 −/−, not‐susceptible, and 2 MUC4 +/+, susceptible, pigs per litter). Within genotype, pigs were fed two different diets: 8.5 (LThr) or 9.0 (HThr) g Thr/kg. Pigs were orally challenged on day 7 after weaning and slaughtered on day 12 or 13 after weaning. Before ETEC challenge, HThr pigs ate more (p  <  0.05). The diet did not affect post‐challenge growth, but HThr tended to increase post‐challenge feed efficiency (p  =  0.087) and overall growth (p = 0.087) and feed efficiency (p = 0.055). Before challenge, HThr pigs excreted less E. coli (p  <  0.05), while after challenge, diet did not affect the number of days with diarrhoea and ETEC excretion. MUC4 +/+ pigs responded to the challenge with more diarrhoea, ETEC excretion and anti‐K88 IgA in blood and jejunal secretion (p < 0.001). HThr pigs had a higher increase of anti‐K88 IgA values in jejunal secretion (p  =  0.089) and in blood (p  =  0.089, in MUC4 +/+ pigs only). Thr did not affect total IgA and IgM values, morphometry of jejunum, goblet cells count in colon, total mucin from jejunum and colon, but varied jejunal goblet cells counts (p < 0.05). In the first two post‐weaning weeks, 8.5 g Thr/kg diet may be not sufficient to optimize initial feed intake, overall feed efficiency and intestinal IgA secretion and to control the gut microbiota in the first post‐weaning week, irrespective of the pig genetic susceptibility to ETEC infection.